Corporate final nodal destination choices in the exodus from Johannesburg Central Business District - Khatleli, Nthatisi (International Structural Engineering Construction Conference (ISEC) Press, 2017)
The opening up of the invisible barriers after the fall of apartheid in South Africa led to massive internal migrations and relocations to bigger cities. Johannesburg as the biggest economic hub not only in South Africa but in Africa, pulled the majority of the new opportunity seekers from across the Africa continent. This uncontrolled influx led to overcrowding, increased crime and grime in the city center of Johannesburg. The loss of value of property in this part of the city led to a lot of corporate organizations relocating to budding economic nodes in and around Johannesburg. The study seeks to understand the processes that were applied in deciding the suitable new Headquarters for these blue chip companies. The new nodes that accommodated the new relocators have over time assumed identities of their own in terms of the type of companies that are mostly found in these areas. Although these identity nuances are not pronounced at first glance, they are accentuated with greater scrutiny. The study sought to see if there is a fit between the independent observation of the characteristics of these locations and the perceived attractors to the blue chip firms. This was achieved by interviewing the executives of these companies and sending emails to some in order to understand the processes and triggers affecting their decisions. It was generally observed that prestige and locational characteristics that complemented the company’s ethos were the overriding triggers in deciding on the final nodal destination.
This paper was presented at the ISEC under the theme: Resilient Structures and Sustainable Construction Edited by Pellicer, E., Adam, J. M., Yepes, V., Singh, A., and Yazdani, S
Keywords: Locational characteristics; Relocation; Blue chip; Triggers; Nodes